Efficiency of Government Spending in Reducing Poverty Rate in Bengkulu Province - Nur Aprida; Azansyah (Formosa Journal of Multidisciplinary Research, 2024)
The study aims to measure the efficiency of local government expenditure in poverty reduction in 10 regencies and cities in Bengkulu Province. The study is quantitative descriptive. Research method applied is Data Envelopment Analysis (DEA) based on input-oriented model with the Variable Retrun to Scale approach. Output is poverty rate. Three inputs used are capital expenditure, goods and service expenditures, and employee expenditure. The results show that out of the 10 regencies and cities in Bengkulu Province in 2019 and 2022 only three regencies are relative efficiency, they are Lebong, Kepahiang, and Bengkulu Tengah. Three peers in Bengkulu Province are Lebong, Kepahiang, and Bengkulu Tengah. The most efficient in 2019 is Lebong regency and in 2022 is Bengkulu Tengah regency. To be efficient, the inefficient regencies and cities government should reduce their expenditure, especially employee expenditure, which is the biggest source of inefficiency.